(untitled) (Libellarium: journal for research in the field of information and related sciences, 2013)
The aim of the paper is to determine the scope and content of Croatian research output in the field of book history, determine which Croatian journals publish papers on book history, the topics covered and the number of scholars who do research in this field. The research was conducted on the corpus of 177 papers published in 17 Croatian journals from 2001 to 2010. The data collected indicates that few journals regularly publish papers on book history, and only one journal explicitly states book history as its major area of interest. Furthermore, it is evident that very few scholars regularly or occasionally do research on book history. The topics covered in selected papers bear witness to a wide range of interests, but only few papers follow recent trends in world book history research. This paper, however, does not cover scholarly or trade monographs and conference proceedings published during the time under investigation, which is one of the limitations of the current research. Still, the output in scholarly and trade journals, which are the main channels of scholarly communication, provides a relevant sample for determining the incidence of book history as a research topic in Croatian science. These findings are the main research contribution of this paper.